Emotional Intelligence as a Predictor of Academic Performance - Arslan Saleem Chughati, Sadia Zaheer, Ghulam Farid, Attaullah Khan Niazi, Muhammad Mujtaba, Asif Islam, Waqas A. Malik (Pakistan Journal of Medical & Health Sciences, 2022)
It is supposed that emotional quotient is directly associated with the performance of the students. To determine the relationship of emotional intelligence on the academic performance, students of 3rd Prof MBBS were selected randomly, who were voluntarily agreed to participate, in this study. Emotional Intelligence Self-Evaluation Questionnaire was filled from them and their result was collected from College records. The data was entered and analyzed using SPSS 21. Statistical difference was determined using Students independent t test taking p-value of 0.05as significant. Correlation was calculated using Pearson Correlation. In this study, 25 students were selected randomly their mean age was 21.76±0.831 years. Among them 17(68%) were female and 8 were (32%) were male students of 4th year MBBS. Overall only 5(20%) of students emotional quotient was at definite strength, in 9(36%) required some development and 11(44%) requires substantial development. on the basis of difference Emotional awareness and Motivation were statistically significantly higher in passed student as compared to students who failed There is association between emotional intelligence and Better academic performance Keywords: Emotional intelligence, Emotional Quotient, Academic Performance, Medical Education, Gender